Analgesic Effect Of Neem (Azadirachta Indica) Seed Oil On Albino Rats - SANJAY KUMAR; DIVYA AGRAWAL; JYOTSNA PATNAIK; SHANTILATA PATNAIK (International Journal of Pharma and Bio Sciences, 2012)
Neem (Azadirachta indica), an indigenous plant is reported to have antidiabetic, anti-inflammatory, antifungal and several other medicinal properties. The present work is undertaken to study the analgesic activity of neem seed oil on albino rats. Neem seed oil was obtained in pure form from Indian Herbs Research Supply Company Limited, Saharanpur, UP. The analgesic activity was tested by the tail flick method using the analgesiometer (Techno.). Neem seed oil in the doses of 0.25, 0.5, 1 and 2 ml/kg body weight was given intraperitoneally to different group of rats. Tail flick latency was measured in seconds before and after the drug injection. Results were compared with morphine and statistically analysed. Neem seed oil showed significant analgesic effect in the dose of 1 and 2 ml/kg. Neem seed oil has dose-dependent analgesic activity.